Characterization of the microenvironment in different immune-metabolism subtypes of cervical cancer with prognostic significance - Lai, Wujiang; Liao, Jinrong; Li, Xiaoxuan; Liang, Peili; He, Liqing; Huang, Keke; Liang, Xiaomei; Wang, Yifeng (Frontiers in Genetics, 2023)
Immune cell infiltration and metabolic reprogramming may have great impact on the tumorigenesis and progression of malignancies. Some studies about cervical cancer have been carried out from the aspects of immunity and metabolism respectively. However, the interaction between these two factors in cervical cancer remains to be clarified. Here we constructed a gene set containing immune and metabolism-related genes and we applied this gene set to molecular subtyping of cervical cancer with the data from the Cancer Genome Atlas (TCGA). Three subtypes were identified with prognostic implications. We performed immune infiltration and metabolism enrichment analysis for the three subgroups and it was found that the C1 subgroup was in an immunosuppressive state with activation of mitochondrial cytochrome P450 metabolism, C2 had poor immune cells infiltration and was characterized by tRNA anabolism, and the C3 subgroup was in an inflammatory state with activation of aromatic amino acid synthesis. In addition, the correlation between tumor infiltrating lymphocytes (TILs) and metabolism was explored. Next, a prognostic prediction model and nomogram based on the immune-metabolic gene set were constructed. The hub genes in the model were validated at single cell resolution. Finally, with immunohistochemistry and in vitro experiments, we found that IMPDH1 can be a therapeutic target of cervical cancer. In summary, our findings suggested novel molecular subtypes of cervical cancer with distinct immunometabolic profiles and uncover a novel therapeutic target.